Case studies on absolute pitch - Makomaska, Sylwia (Archives of Acoustics, 2007)
Absolute pitch (AP) seems to be one of the most remarkable phenomena of the longtermauditory memory. AP possessors can identify or also produce musical pitches (e.g. C,C#, D, etc.) without using any external reference tone. The aim of the present investigationwas to determine the prevalence of AP in students of Polish music schools. In the first partof the investigation pitch-naming test with piano tones was applied to about 1100 subjects.The test was accompanied by a questionnaire including questions about the details of musicaleducation, familial aggregation of AP and the features of musical hearing. In the second parttests with tones of various timbre were applied to 31 students who had identified more than50% pitch values in the first test. In the present paper discussed are individual cases of variousforms of AP.